Konflik Dan Ambiguitas Peran: Faktor-Faktor Penentu Dalam Kinerja Auditor - Gilbert Johan Martin Sinaga (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
This study aims to examine the effect of role conflict and role ambiguity on auditor performance in Pekanbaru City. This study uses a quantitative causality approach to answer the formulation of problems and research hypotheses. The population in this study were all auditors who worked at KAP Pekanbaru city and were registered in the Directory of Public Accounting Firms issued by the Indonesian Institute of Accountants. The sampling technique chosen was purposive sampling. The number of samples obtained was 70 auditors. The type of data used is primary data and data collection techniques using questionnaires. Data analysis using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) with SmartPLS 4.0 software. The novelty in this study is that there are still few studies that focus on the performance of KAP auditors in Pekanbaru City and several previous studies also show a research gap. The results obtained are role conflict and role ambiguity have a significant effect on auditor performance.